Synthesis and Study of Antifungal Properties of New Cationic Beta-Glucan Derivatives - Kamil Kaminski; Magdalena Skora; Paweł Krzyściak; Sylwia Stączek; Agnieszka Zdybicka-Barabas; Małgorzata Cytryńska (MDPI AG, 2021)
The interaction of positively charged polymers (polycations) with a biological membrane is considered to be the cause of the frequently observed toxicity of these macromolecules. If it is possible to obtain polymers with a predominantly negative effect on bacterial and fungal cells, such systems would have great potential in the treatment of infectious diseases, especially now when reports indicate the growing risk of fungal co-infections in COVID-19 patients. We describe in this article cationic derivatives of natural beta-glucan polymers obtained by reacting the polysaccharide isolated from Saccharomyces boulardii (SB) and Cetraria islandica (CI) with glycidyl trimethyl ammonium chloride (GTMAC). Two synthesis strategies were applied to optimize the product yield. Fungal diseases particularly affect low-income countries, hence the emphasis on the simplicity of the synthesis of such drugs so they can be produced without outside help. The three structures obtained showed selective anti-mycotic properties (against, i.e., Scopulariopsis brevicaulis, Aspergillus brasiliensis, and Fusarium solani), and their toxicity established using fibroblast 3T3-L1 cell line was negligible in a wide range of concentrations. For one of the polymers (SB derivative), using in vivo model of Aspergillus brasiliensis infection in Galleria mellonella insect model, we confirmed the promising results obtained in the preliminary study.